The limitations in implementing and operating a rapid response system. Issue 10 (October 2016) - Subramaniam, A.; Botha, J.; Tiruvoipati, R.
Abstract : Despite the widespread introduction of rapid response systems (RRS)/medical emergency teams (MET), there is still controversy regarding how effective they are. While there are some observational studies showing improved outcomes with RRS, there are no data from randomised controlled trials to support the effectiveness. Nevertheless, the MET system has become a standard of care in many healthcare organisations. In this review, we present an overview of the limitations in implementing and operating a RRS in modern healthcare.